A contribution to Centaurea sect. Acrocentron (Asteraceae) from Iran - Ranjbar, Massoud; Negaresh, Kazem (Phytotaxa, 2013)
Centaurea sanandajensis is described and illustrated as a new species from Kurdestan Province, W Iran. The characters that distinguish the new species from its nearest relative C. longipedunculata are given. In addition, C. elegantissima is reported as new to Iran, and its chromosome number (2n = 2x = 22) is counted for the first time. The description of C. elegantissima is completed with the characters of mature achenes, and its differences from the nearest relative C. kandavanensis are summarized. The geographical distribution of discussed species is presented.